EVALUATION AND SELECTION OF SALINITY TOLERANT LINES IN BRASSICA NAPUS USING CORRELATION AND PATH COEFFICIENT ANALYSIS - S. Kanwal; R. Qamar; S. Jamil; M. H. N. Tahir (Journal of Animal and Plant Sciences, 2023)
Genetic variation and varied response of genotypes with erraticsalt tolerance enable us to recognize and utilize the underlying physiological and biochemical mechanisms in development of salinity tolerant cultivars. In the present studies, ten lines viz., B-56, BLBN, G-96, R-3, RBJ-8007, ZMR-1, ZMR-2, ZNR-1, ZMM-5, and 23627, and six testers i.e., Faisal, Shiralee, Laclone, Long, Legend, and ZMR-3 were collected and crossed in a line by tester fashion. The resultant F1 crosses and their parental genotypes were assessed at maturity phase in a pot experiment under factorial structured CRD. Recorded data on morphological traits were analyzed to assess the genetic variability in breeding material, association among traits, and their direct and subsidiary effects on seed and oil yield. Analysis of variance showed the presence of significant genetic variability within and among the salinity treatments. Parental genotypes were found significantly different for Na+/K+ ratio, proline contents, osmotic potential, primary branches, and oil contents under all treatments. Entries and parents vs. crosses differed significantly for most of the traits indicating that breeding material possesses genetic variability which may be exploited in future breeding program for effective upgradation of yield and salinity tolerance. Correlation and path analysis exposed that silique per plant, seeds per silique, oil content, thousand seeds weight, and days to 50% maturity might be used as criteria of selection for development of salinity tolerant types with higher yield. Morphological traits showed significant association with yield per plant under salt stress conditions. These associations can be useful in sorting salt tolerant and sensitive high yielding genotypes. Accumulation of proline and Na+/K+ ratio may also be chosen as selection criteria for targeting salinity tolerance in the future breeding program. Screening of salt tolerant lines and subsequent development of salinity tolerant cultivars may be helpful in inclusion of salt effected area’s under Brassica cultivation thereby increasing the local production of edible oil in Pakistan.
Keywords: salinity; correlation; path coefficient; genetic variability; morphological; proline; Na+/K+